2015
DOI: 10.2967/jnumed.115.155143
|View full text |Cite
|
Sign up to set email alerts
|

Global and Regional Myocardial Innervation Before and After Ablation of Drug-Refractory Ventricular Tachycardia Assessed with 123I-MIBG

Abstract: Cardiac innervation is a critical component of ventricular arrhythmogenesis that can be noninvasively assessed with 123 I-MIBG. However, the effect of ventricular tachycardia (VT) ablation on global and regional left ventricular sympathetic innervation and clinical outcomes has not been previously assessed. Methods: In this prospective, single-center feasibility study, 13 patients with cardiomyopathy (n 5 9 ischemic, n 5 4 nonischemic) who were scheduled to undergo ablation of drug-refractory VT underwent 15-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The dual-isotope acquisition protocol using 201 Tl and 123 I-mIBG is well documented on conventional Anger cameras, using the triple-energy window [25] for scatter and crosstalk correction. Simultaneous perfusion and sympathetic innervation imaging with 123 I-mIBG and 99m Tc-labelled tracers enables the evaluation of innervation-flow mismatch and may provide valuable information to target the trigger zone in the setting of ventricular arrhythmia [4, 26]. In a recent study, Gimelli et al [11, 27] using sequential 123 I-mIBG and 99m Tc-tetrofosmin myocardial SPECT demonstrated a relevant association between innervation derangement ( 123 I-mIBG) and myocardial synchronicity ( 99m Tc-tetrofosmin).…”
Section: Discussionmentioning
confidence: 99%
“…The dual-isotope acquisition protocol using 201 Tl and 123 I-mIBG is well documented on conventional Anger cameras, using the triple-energy window [25] for scatter and crosstalk correction. Simultaneous perfusion and sympathetic innervation imaging with 123 I-mIBG and 99m Tc-labelled tracers enables the evaluation of innervation-flow mismatch and may provide valuable information to target the trigger zone in the setting of ventricular arrhythmia [4, 26]. In a recent study, Gimelli et al [11, 27] using sequential 123 I-mIBG and 99m Tc-tetrofosmin myocardial SPECT demonstrated a relevant association between innervation derangement ( 123 I-mIBG) and myocardial synchronicity ( 99m Tc-tetrofosmin).…”
Section: Discussionmentioning
confidence: 99%
“…3D reconstructions of myocardial innervation were created using Amira 5.4.2 software (Visage Imaging). On each 2-dimensional 123 I-MIBG SPECT slice, areas of abnormally innervated myocardium (,50% tracer uptake) were determined visually by 2 masked, experienced cardiac nuclear medicine physicians with previously demonstrated intraobserver or interobserver variability of less than 10% (8). From the sequential 2-dimensional datasets, individual 3D innervation maps were created for each of the patients in the Amira environment (Figs.…”
Section: D 123 I-mibg Cardiac Map Reconstructionmentioning
confidence: 99%
“…Both structural imaging and functional imaging demonstrated a good to moderate correlation with the voltage-defined VT substrate. However, small to moderate degrees of mismatch between structural imaging (CMR/CT) or functional imaging ( 18 F-FDG PET/ 123 I-MIBG innervation) and EAM suggested that postischemic adaptation may be a more complex, heterogeneous process affecting structural and functional properties of the VT substrate to variable degrees (1,3,(7)(8)(9)(10). To our knowledge, a comparison of structural and functional imaging properties and determination of their correlation with EAM/VT substrate data have not yet been performed.…”
mentioning
confidence: 99%
“…4,6,11,12 Accordingly, it has been recently reported that the specific geographical distribution of 123 I-MIBG uptake at myocardial SPECT can be used to guide the performance and predict the results of the procedures of transcatheter ablation of ventricular arrhythmias. 18,19 Until now, despite the obvious appeal of a dualisotope myocardial innervation/perfusion imaging protocol, most of the studies in whom it was employed have performed two separate acquisitions to obviate the development of possible scatter artifacts due to the crosstalk between the photons of the two radionuclides. 11,12 In fact, current scatter correction algorithms may consistently reduce the count statistics of a SPECT scan by rejecting the photons that fall in the predefined energy sub-windows of the ''lower energy'' isotope (i.e., 201 Tl), thus reducing the overall image quality obtained with tradition cardiac cameras.…”
Section: See Related Article Pp 1361-1369mentioning
confidence: 99%